Estructuración y operativización del proyecto de expansión de Carrusel Sport - Bastidas Valle, Karla Monserrath (2006)
The thesis is divided into chapters sies, that help us pinpoint the process of expanding the company Carousel Sport, the same dedicated to the manufacture of athletic apparel, especially sports uniforms.